Quassinoids from Eurycoma longifolia as Potential Dihydrofolate Reductase Inhibitors: A Computational Study - Yunos, Nurhanan M.; Al-Thiabat, Mohammad Gasem; Sallehudin, Nor Jannah; Wahab, Habibah A (Current Pharmaceutical Biotechnology, 2024)
Background: Quassinoids are degraded triterpene compounds that can be obtained from various species of the Simaroubaceae plant family, including Eurycoma longifolia. Quassinoids are the major compounds in E. longifolia, and they are known to have various medicinal potentials, such as anticancer and antimalarial properties. Dihydrofolate reductase (DHFR) was reported to be one of the important targets for certain anticancer and antimalarial drugs. Twelve quassinoids from E. longifolia were identified to have anticancer effects based on their IC50 values. This study aimed to evaluate the interactions of these twelve quassinoids with DHFR via Autodock 4.2 software and Biovia Discovery Studio Visualiser. Methods: Twelve quassinoids from E. longifolia and their interactions with DHFR were evaluated via Autodock 4.2 software and Biovia Discovery Studio Visualiser. Their drug-likeness and pharmacokinetic properties were also assessed using the ADMETlab 2.0 program. Results: The molecular docking results showed that eleven quassinoids showed better docking scores than methotrexate, in which the binding energy (BE) of these quassinoids ranged from - 7.87 to -9.58 kcal/mol. Their inhibition constant (Ki) ranged from 0.095 to 1.71 μM. At the same time, the BE and Ki values for methotrexate were -7.80 kcal/mol and 1.64 μM, respectively. Conclusion: From the analysis, 6-dehydrolongilactone and eurycomalide B are among the twelve compounds that showed great potential as hit-to-lead compounds based on the docking score on DHFR, drug-likeness, and ADMET properties. These results suggest a great potential to pursue validation studies via in vitro and in vivo models.
Keywords: cancer